Peningkatan Pemahaman Pembuatan Media Pembelajaran Guru PAUD Melalui Pemanfaatan Limbah Kayu - Nirmala, Ine; Sudrajat, Ajat; Sholeh, Slamet; Ashilah, Neng Gina; Nanih, Nanih (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Jatimulya Village, one of the villages in Karawang Regency, has a Garbage Bank which receives plastic waste, plastic bottles or plastic cups, paper, newspapers, cardboard, and wood scraps from the community every day. Leftover wood waste from production or wood products that are no longer used if not used properly will cause serious problems for the environment. Pretest results on 10 teachers from 5 early childhood education programs found 40% of teachers were still unsure and did not know about the durability of media and had never made media from wood waste. This community service activity uses socialization and hands-on practice in making mathematics learning media made from wood. After participating in this socialization and training activity, it was shown that there was an 80% increase in knowledge and understanding of the use of wood waste as media material for early childhood mathematics learning. This activity motivates early childhood education programs teachers to innovate by using wood waste in the surrounding environment to become a media that can be used for learning, especially mathematics for early childhood.